Sclerosing thymoma with numerous coarse calcifications - Hironori Oyamatsu; Takaki Fujimura; Takehiko Okagawa; Seijirou Niimi (Respirology Case Reports, 2024)
Key message This patient is the youngest among the previously reported sclerosing thymoma cases, and the resected mass contained numerous coarse calcifications due to dystrophic calcification. This is an unprecedented and extremely rare case.